Contemporary Challenges in Environmental Governance: Technology, governance and the social licence. (12th December 2016) - Cullen‐Knox, Coco; Eccleston, Richard; Haward, Marcus; Lester, Elizabeth; Vince, Joanna
Abstract: The process through which societal actors can exert direct influence on the behaviour of organizations has gained increasing attention over the past two decades and is increasingly referred to as 'social licence' or 'social licence to operate'. This paper documents the rise of social licence and analyses the relationship between information and communication technology (ICT), governance and the social licence. We argue that contemporary social licence and the increasingly prominent role societal actors have in private governance has been facilitated by technological innovation in the fields of media and communications, allowing interest groups to have a far greater reach, and direct interaction and engagement with the public, other interest groups and the industries concerned. Now, a larger population can rapidly contest traditional practices regardless of national borders, the issue concerned or the actors involved. The unpredictable, dynamic and subjective nature of social licence has prompted concerns regarding legitimacy of stakeholders, the information they disseminate and outcomes they promote. Subsequently, in an attempt to maintain political and corporate legitimacy, business interests are demanding more adaptable regulatory regimes. These political dynamics are resulting in the proliferation of network style governance that can adapt and cope with changing information, attitudes, values and beliefs. As a result a new era of experimentation and trialling alternative governance regimes has been born. Copyright © 2016 John Wiley & Sons, Ltd and ERP Environment